Practical Development Of An Open Architecture Personal Computer-Based Numerical Control (Oapc-Nc) System [TJ1189. P535 2005 f rb]. - Pang, Tze Hong (2005)
In this research, an open architecture personal computer-based numerical control (OAPC-NC) system that can generate G-code was developed.